Overexpression of a Grapevine Sucrose Transporter (VvSUC27) in Tobacco Improves Plant Growth Rate in the Presence of Sucrose In vitro - Cai, Yumeng; Tu, Wenrui; Zu, Yunyun; Yan, Jing; Xu, Zimo; Lu, Jiang; Zhang, Yali (Frontiers in Plant Science, 2017)
The import of sugar from source leaves and it further accumulation in grape berries are considerably high during ripening, and this process is mediated via sucrose transporters. In this study, a grape sucrose transporter gene, VvSUC27, located at the plasma membrane, was transferred to tobacco (Nicotiana tabacum). The transformants were more sensitive to sucrose and showed more rapid development, especially roots, when cultured on MS agar medium containing sucrose, considering that the shoot/root dry weight ratio was only half that of the control. Moreover, all transformed plants exhibited light-colored leaves throughout their development, which indicated chlorosis and an associated reduction in photosynthesis. The total sugar content in the roots and stems of transformants was higher than that in control plants. No significant difference was observed in the leaves between the transformants and control plants. The levels of growth-promoting hormones were increased, and those of stress-mediating hormones were reduced in transgenic tobacco plants. The qRT-PCR analysis revealed that the expression of VvSUC27 was 1000 times higher than that of the autologous tobacco sucrose transporter, which suggested that the markedly increased growth rate of transformants was because of the heterogeneously expressed gene. The transgenic tobacco plants showed resistance to abiotic stresses. Strikingly, the overexpression of VvSUC27 leaded to the up regulation of most reactive oxygen species scavengers and abscisic acid-related genes that might enable transgenic plants to overcome abiotic stress. Taken together, these results revealed an important role of VvSUC27 in plant growth and response to abiotic stresses, especially in the presence of sucrose in vitro.